Water, Sanitation, and Hygiene: A Global Imperative for Health - Kishore, Surekha; U, Venkatesh; Verma, Shikhar Kishore; Verma, Shival Kishore; Walia, Parteek (Indian Journal of Community Health, 2023)
Clean water, proper sanitation, and hygiene (WASH) can have a significant impact on human health. Lack of financial resources prevent developing nations from making investments in WASH infrastructure, such as water treatment plants and sanitation facilities. Achieving universal access to clean water and sanitation is hampered by poor governance and insufficient policy frameworks. Governments, civil society organizations, and the private sector need to collaborate to invest in infrastructure and technology, promote good hygiene practices, and undertake education and awareness-raising programmes in order to ensure that everyone has access to clean water and sanitation.